COMPARISON OF MAZE GENERATION ALGORITHMS - Boldovs, Igors; Vinogradovs, Jurijs; Grabusts, Pēteris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
The author in this work provides insight into the Maze generation. Themes which are discussed are Eller’s algorithm, Kruskal’s algorithm and Recursive backtracking algorithm. All this algorithms were compared.